Development of tolerance to chemokine receptor antagonists: current paradigms and the need for further investigation - Grudzien, Patrick; Neufeld, Henry; Ebe Eyenga, Mbasogo; Gaponenko, Vadim (Frontiers in Immunology, 2023)
Chemokine G-protein coupled receptors are validated drug targets for many diseases, including cancer, neurological, and inflammatory disorders. Despite much time and effort spent on therapeutic development, very few chemokine receptor antagonists are approved for clinical use. Among potential reasons for the slow progress in developing chemokine receptor inhibitors, antagonist tolerance, a progressive reduction in drug efficacy after repeated administration, is likely to play a key role. The mechanisms leading to antagonist tolerance remain poorly understood. In many cases, antagonist tolerance is accompanied by increased receptor concentration on the cell surface after prolonged exposure to chemokine receptor antagonists. This points to a possible role of altered receptor internalization and presentation on the cell surface, as has been shown for agonist (primarily opioid) tolerance. In addition, examples of antagonist tolerance in the context of other G-protein coupled receptors suggest the involvement of noncanonical signal transduction in opposing the effects of the antagonists. In this review, we summarize the available progress and challenges in therapeutic development of chemokine receptor antagonists, describe the available knowledge about antagonist tolerance, and propose new avenues for future investigation of this important phenomenon. Furthermore, we highlight the modern methodologies that have the potential to reveal novel mechanisms leading to antagonist tolerance and to propel the field forward by advancing the development of potent “tolerance-free” antagonists of chemokine receptors.